Terminology study on vibration-based condition monitoring technique - Chatzitheodorou, Konstantinos; Kappatos, Vassilios (Vibroengineering Procedia, 2020)
In this paper, we present the initial results of a terminology study on a vibration-based condition monitoring technique to support the research community. We automatically export terminologies from domain specific textual corpora and a team of subject matter experts validates and revises 20 typical terms. Our goal is twofold; (i) to standardize terminology for the domain of vibration since different groups use different definitions of commonly used terms and (ii) to distinguish the specific terminology from the general terminology or from the terminology of other mechanical areas. We intended to serve the needs of a wide range of user groups such as subject matter experts who sometimes need to ascertain the meaning of an unknown term or concept. To date, there is no similar work or initiative that could be integrated, reused or extended.